Herbicide resistance in the Canadian prairie provinces : Five years after the fact - Morrisson, I.N.; Devine, M.D. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1994)
Herbicide resistance was first recognized as a problem on the Canadian Prairies in 1988 when trifluralin-resistant green foxtail (Setaria viridis) was reported in Manitoba, and chlorsulfuron-resistant chickweed (Stellaria media) and koehia (Kochia scoparia) in Alberta and Saskatchewan, respectively. Since then, the number of resistant weeds has increased to include wild oats (Avena fatua) resistant to triallate and to aryloxyphenoxypropionate and cyclohexanedione (group 1) herbicides, green foxtail to group 1 herbicides, Russian thistle (Salsola pestifer) and wild mustard (Sinapis arvensis) to sulfonylurea and imidazolinone (group 2) herbicides, and wild mustard to growth regulator (group 4) herbicides. The levels and patterns of cross-resistance to chemicals in groups 1 and 2 vary widely among different populations, with resistance factors [resistant to susceptible (R:S) ratios] derived from dose response curves typically ranging from < 2 to > 150. Group 1 resistance in green foxtail and group 2 resistance in chickweed and kochia populations are due to reduced sensitivities of the target enzymes, acetyl coenzyme-A carboxylase (ACCase) and acetolactate synthase (ALS), respectively. The mechanisms of resistance in the other species including wild oats resistant to ACCase inhibitors (group 1 ) and to triallate/difenzoquat (group 8) are unclear. At present, the only instance of multiple resistance in western Canada is green foxtail resistant to chemicals in both groups 1 and 3 (ACCase inhibitors and dinitroanilines). Future concerns focus mainly on the increasing seriousness of group 1 and 8 resistance across the Prairies, and on the possibility of selecting for multiple resistance in weeds such as green foxtail for which there are few remaining effective control options.